Analisis Personal Branding Prabowo Subianto Melalui Media Sosial TikTok Partai Gerindra - Novitasari, Arasyida; Angeline; Septiani, Anita Dwi; Stanley, Jason Nick; Susanto, Silvia Claretta; Sundah, Pierre Mauritz (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
The phenomenon of personal branding is increasingly evident on social media, with TikTok emerging as one of the most popular digital platforms for this purpose. Its extensive user base enables individuals to reach a wide audience through visual and audiovisual content, fostering interaction with followers. Prabowo Subianto, the Minister of Defense and a potential candidate for the 2024 Presidential Election, is one political figure utilizing TikTok to build personal branding. This study aims to describe Prabowo Subianto's personal branding through the @partaigerindra TikTok account. Employing qualitative descriptive research methods, the study delves deeply into data to provide insights into Prabowo Subianto's personal branding phenomenon on TikTok. Findings reveal that Prabowo's personal branding incorporates the eight laws proposed by Montoya and Vandehey. His efforts have generated a positive perception, evident through netizens' comments on Gerindra Party's posts. The strength of Prabowo's personal branding on TikTok serves as a competitive advantage for the 2024 Election.